The degree to which primary school teachers practice active learning strategies from the point of view of school principals (Journal of the College of Basic Education, 2022)
The study aimed to identify ("the degree to which primary school teachers practice active learning strategies from the point of view of school principals") in the province of Baghdad - as the researcher used the descriptive survey method to suit the subject of the research. Baghdad governorate center for the academic year (2021-2022) AD. The research sample amounted to (60) male and female directors, 30 (males) and 30 (females). The researcher adopted the (Al-Araydah, 2016) scale, which consisted of (30) items, and distributed it to the research sample consisting of (60) male and female directors, and the validity was verified. The questionnaire was presented to a group of experts and they supported the validity of the questionnaire. Also, the stability of the questionnaire was verified through the midterm segmentation, which amounted to (0.92) and after correcting it with the Spearman-Brown equation, the reliability coefficient became (0.95). search:After extracting the general weighted mean of the domains, it was found that the degree to which primary school teachers practice active learning strategies got a (large) degree, as the general weighted mean of these domains as a whole was reached, and this result is consistent with the weighted mean of the responses of the research sample members. Active learning in the second Rusafa district is to a large extent, given that the weighted mean of this axis falls within the degree of (large) practice.The researcher made several recommendations, including:1- The necessity of employing active learning strategies in developing some skills related to the participation of others in ideas, communication, and the distribution and exchange of roles; This is done by developing the spirit of cooperation and love of participation among students2- The necessity of involving students in planning educational processes in their schools and developing their relationship with societyIn light of the results of the current research, the researcher suggests the following:- Conducting similar studies to determine the degree to which teachers practice active learning strategies in another stage of study.Providing all means of support to encourage teachers working in the educational field to use active learning strategies.